Boolean Spider Monkey Optimization Assisted Routing Integrated with Wireless Sensor Network - et. al., Ashwini, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Wireless Sensor Network (WSN) offers greater flexibility in network deployment, especially when powered by batteries. It offers solutions to the sensor nodes' energy consumption as it mainly operates as devices with faster data acquisition. Hence, it is difficult for the sensor nodes to carry such a computational burden from the source nodes to the target base station or the internet gateway. It is essential to maintain the routing paths as well as the balance of the sensor nodes. In this paper, we propose a Boolean Spider Monkey Optimization (BSMO) routing on WSNs is developed to maintain the stable routing path that matches the speed of input data acquisition. The sensor nodes help in data collection and acquisition and WSNs routes the data collected via hops between the source and sink nodes. The BSMO is responsible for controlling the data routing and matches the routing speed with data acquisition speed. Hence, the network is maintained in a stabilized condition. The simulation results are estimated in terms of average delay, throughput, and network energy efficiency. The result shows